The Influence of Pedagogical Methods and The Use of Digital Tools on Perceived Competencies and Preparation for The Job Market of Students In Digital Marketing - Mohamed, Bouaddi (TECHNOVATE: Journal of Information Technology and Strategic Innovation Management, 2025)
This study investigates the impact of pedagogical methods, the use of digital tools, and educational levels on the perceived competencies and job market readiness of digital marketing students in Morocco. A quantitative approach was employed, involving a sample of 250 students evenly divided between License’s and Master's programs. Data were collected via a structured questionnaire. Results indicate that students who engaged in practical courses reported higher job market preparedness compared to those in theoretical courses. A significant positive correlation was found between the use of digital tools and perceived competencies. Additionally, ANOVA analysis revealed that Master's students perceived their competencies more positively than Bachelor's students. These findings suggest a need for enhanced practical learning opportunities and greater integration of digital tools in curricula, along with stronger industry partnerships to better prepare students for market demands.